Seagrass Ecosystems in Eastern Indonesia: Status, Diversity, and Management Challenges - Supriyadi, Indarto Happy; Iswari, Marindah Yulia; Rahmawati, Susi; Riniatsih, Ita; Suyarso, Suyarso; Hafizt, Muhammad (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2024)
Seagrass beds have roles and benefits in shallow water ecosystems, including producers of organic matter, habitats for various marine biota, and providing services that are beneficial for the fishing community. However, increasing development activities in coastal areas, have decreased their valuable roles, which also affects damage in seagrass beds in Indonesian waters. Therefore, information on species diversity and seagrass conditions, especially in East Indonesian waters, is needed. This paper aims to provide information as the initial study of the distribution of species diversity, conditions of seagrass beds, and challenges of seagrass management in eastern Indonesia. This study collected primary and secondary data from several data sources from seagrass monitoring and research activities. The assessment of conditions and categories of seagrass cover refers to the Decree of the state minister for the Environment (KMN-LH) of 2004 No. 200 and the 2017 seagrass monitoring guidelines. As a result of 24 monitoring locations ten species were found indicating that Eastern Indonesia has high species diversity. The results at 24 locations can be categorized as healthy seagrass conditions in six locations (25%) and around 16 locations (67%) as less healthy. Monitoring results after 2015 are predicted to change the diversity and seagrass conditions. The challenges of seagrass management in Eastern Indonesian waters, including the coastal environment changes, need to increase public knowledge and understanding of the role, function, and benefits of seagrass. Also, replanting and enhancement of seagrass-protected areas are essentially needed by the local government.